2016
DOI: 10.1061/(asce)gt.1943-5606.0001435
|View full text |Cite|
|
Sign up to set email alerts
|

Stress-Strain Response and Dilatancy of Sandy Gravel in Triaxial Compression and Plane Strain

Abstract: The strength and stress-dilatancy of uniform sands has been studied extensively in geotechnical investigations, and practitioners can draw on a wealth of previously reported data for the estimation of their volumetric response. However, the suitability of accepted stressdilatancy theory and empiricism has not been evaluated for well-graded gravelly soils. Axisymmetric, isotropically consolidated drained compression, and pure shear, plane strain quasi-K 0 consolidated drained tests were performed on well-graded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The analysis of these static triaxial tests allows independent estimation of the friction angles and apparent cohesion parameters at ϕ ’ = 42° and c = 45 kPa, in accordance with previous studies [38]. The differences between the results arising from the effective stress plot (Figure 3b) and the Coulomb–Mohr analysis (Figure 4c) happen due to the nonlinear results of triaxial tests.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The analysis of these static triaxial tests allows independent estimation of the friction angles and apparent cohesion parameters at ϕ ’ = 42° and c = 45 kPa, in accordance with previous studies [38]. The differences between the results arising from the effective stress plot (Figure 3b) and the Coulomb–Mohr analysis (Figure 4c) happen due to the nonlinear results of triaxial tests.…”
Section: Resultssupporting
confidence: 85%
“…The tests did not allow one to obtain the cohesion parameter c. Friction angles and cohesion coefficients of natural aggregates with C U = 6.6 and a grain size distribution similar to the RCAs studied here were previously found to be around ϕ = 39.6° and c = 0 (see [ 36 , 37 ]). Studies on sandy gravel subjected to triaxial compression led to the estimation of the friction angles in the range 39° < ϕ < 48° to NAs, depending on the relative density changes during the consolidation step [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings illustrate that particle shape can have significant impacts on the susceptibility to liquefaction, undrained shear strength, and critical-state strength of sands (Rousé et al 2008;Tsomokos and Georgiannou 2010;Suh et al 2017) since the particle shape affects the assembly density (Cho et al 2006;Shin and Santamarina 2013;Zheng and Hryciw 2016) and influences fabric stability at the contact scale (Yang and Wei 2012). Stress-dilatancy behavior is an intrinsic property of granular materials (Bolton 1986;Salgado et al 2000;Zhao and Evans 2009;Strahler et al 2016). However, the effects of particle shape on the strength, dilatancy, and stressdilatancy response have not been fully studied.…”
Section: Introductionmentioning
confidence: 95%
“…Macroscopic mechanical behaviors of natural granular soils are significantly influenced by (1) internal factors, such as particle strength (Kuwajima et al 2009; Shipton and Coop 2012; Wei and Yang 2014), particle size (Varadarajan et al 2003;Frossard et al 2012;Dai et al 2016;Zhang et al 2016;Zhou et al 2016), particle size distribution (Kokusho et al 2004;Li et al 2013;Wang et al 2013;Ovalle et al 2014;Dai et al 2016;Strahler et al 2016;Xiao et al 2018a), particle shape (Cho et al 2006;Yang and Luo 2015;Altuhafi et al 2016), and density (Been et al 1991;Wan and Guo 1998;Xiao et al 2014a); and (2) external factors, such as confining pressure (Charles and Watts 1980;Chiu and Fu 2008;Xiao et al 2016aXiao et al , 2017Strahler et al 2018), stress path (Vaid and Sasitharan 1992;Xu et al 2012;Xiao et al 2016b), loading mode (Chu and Wanatowski 2009), saturation (Oldecop and Alonso 2001;Yamamoto et al 2009;Ovalle et al 2015), and drainage conditions (Chu et al 2012). Moreover, addition of fines (i.e., particle size finer than 74 μm) in different fractions to clean sands can greatly affect the strength, dilatancy, and critical-state behavior of these sand-fines mixtures (Thevanayagam 1998;Salgado et al 2000;Polito and Martin 2001;Chiu and Fu 2008;…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that particle features have well-known effects on the characteristic behaviour of granular materials, including strength of the particle [23,37,47], size of the particle [9,12,43,54,56], particle size distribution [9,20,25,31,39,46,48] and shape of the particle [2,6,51]. Recently, research interest has been growing on exploring the particle scale characteristics of granular materials considering an in-depth understanding of the microscopic parameters (e.g.…”
Section: Introductionmentioning
confidence: 99%